PERAN SATUAN POLISI PAMONG PRAJA DALAM MENINGKATKAN KETERTIBAN PEDAGANG KAKI LIMA - Rini Andriani; Lina Marlina (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
This research was based on the background of the problem of order that is, there were still street vendors who sell in the west plaza of Serang city. The purpose of this study was to determine the role of Satpol PP in increasing orderliness of street vendors which were still sold in the west plaza of Serang city. This research method was descriptive with the factual depiction, data in the form of expressions, languages ​​, and discourses that were precise and systematic. Qualitative research is research that is used to examine the scientific condition of the object, where the researcher was a qualitative instrument. The results of this study indicate the role of satpol PP in increasing orderliness of street vendors has been good at minimizing street vendors who sell in the west square of Serang city. The conclusion of this research confirms that the street vendors were not allowed to sell in the west square area of Serang city and to minimize the stubborn street vendors, the Satpol PPcarrying out the raids routine every day. The suggestion in this research was that the Satpol PP keeps monitoring and doing raids routine every day so that the street vendors will not sell in the west square of Serang city.